Pavement engineering for forest roads : development and opportunities - Heinimann, Hans Rudolf (Array, 2020)
Pavement is an essential component of roads as it carries the traffic and provides the required riding comfort. Considering that numerous forest roads are approaching their end of life, the critical issue is identifying the best rational pavement design methods to reengineer existing and build new pavement structures. The purpose of this contribution was (1) to review the big development lines of pavement systems, (2) to have a critical look at the pavement engineering framework, and (3) to bring selected empirical design equations into a comparable scheme. The study resulted in the following significant findings. First, the Trésaguet and McAdam pavement systems represented the state of the art from the beginning of a formal forest road engineering discipline at the beginning of the 19th century and remained for almost 150 years. Second, the emergence of soil mechanics as a scientific discipline in the 1920s resulted in the optimal grading of aggregates and improvement of soils and aggregates with binders, such as lime, cement, and bitumen. Third, the rational pavement design consists of five essential components: (1) bearing resistance of the subsoil, (2) bearing resistance of the pavement structure, (3) lifecycle traffic volume, (4) uncertainties that amplify deterioration, and (5) the limit state criterion, defining thresholds, above which structural safety and serviceability are no longer met. Fourth, rational, formal pavement design approaches used for forest roads were "downsized" from methodologies developed for high-volume roads, among which the approaches of the American Association of State Highway and Transportation Officials (AASHTO) and US Army Corps of Engineers (USACE) are of primary interest. Fifth, the conversion of the AASHTO '93 and USACE '70 methods into the SI system indicated that both equations are sensitive to soil bearing resistance, measured in California Bearing Ratio (CBR).